The Future of Robotics Process Automation in Shipping Line Business to Achieve Better Customer Satisfaction - Mhatre, Prashant (Digital Repository of Theses, 2025)
This research is being conducted to explore and understand the global Shipping lines business, their customer-facing issues, and how they can be satisfied with the service by using the Robotic Process Automation (RPA) tool. This study aims to explore the implementation and impact of RPA in the shipping industry, focusing on operational efficiency, customer satisfaction, and organizational challenges related to its adoption. In this study, survey-based quantitative as well as qualitative approaches were employed, gathering responses from professionals in the shipping industry. The study analyzed the adoption rate of RPA, its influence on productivity, and the perceptions of its benefits and challenges. In this study, the data collection involved self-structured questionnaires and interviews with the respondents. The collected dataset was analyzed using statistical methods such as frequency analysis and one sample chi-square through SPSS (Statistical Packages for Social Sciences), while thematic analysis was used to analyses the qualitative data. The study finds that overall, RPA has a positive impact on organizational throughput by eliminating mundane clerical work that includes, but is not limited to documentation, shipment tracking, and invoicing. It also benefits customer satisfaction since customers are presented with real-time information and reducing errors. Still, there are several difficulties, including the high costs of initial preparations, the negative attitudes of employees, and the requirement of leadership engagement. The study indicated that integrating RPA with other superior technologies, such as AI, can expand its benefit, but most firms have no definite plans for how to implement these interconnections. So, although RPA has many benefits for enhancing the work and helping clients in the shipping industry, its use is bounded by implementation challenges. Looking at leadership awareness, the issue of employees’ resistance and the AI technology assimilation are important. Hence, based on the current research, the following suggestions are proffered with regards to how the shipping companies can further enhance the utilisation of RPA to achieve better utilisation returns and effectiveness, Evaluation and involvement of leadership, Training of its workers, Other AI applications that can augment the value of RPA and generate better Returns On Investment (ROI).